Group consensus and minority influence : implications for innovation - Dreu, Carsten K. W. de; Vries, Nanne K. de (Blackwell, 2001)
Reviews the impact of majority and minority influence on attitude change and persuasion, on individual and group problem solving, organizational processes, and on group performance and innovation. The book also provides insights on how to work more effectively with groups in applied situations.